Regulation of amino acid metabolism in Aphis gossypii parasitized by Binodoxys communis - Xue, Hui; Zhao, Yunyun; Wang, Li; Zhu, Xiangzhen; Zhang, Kaixin; Li, Dongyang; Ji, Jichao; Niu, Lin; Cui, Jinjie; Luo, Junyu; Gao, Xueke (Frontiers in Nutrition, 2022)
The vast majority of parasitoids are capable of precise and meticulous regulation of nutrition and metabolism within the host. An important building block of life, amino acids are critical to the development of parasitoids. To date, research on how parasitoids regulate host amino acid metabolism remains limited. In this study, Aphis gossypii and its dominant parasitoid Binodoxys communis were used as a study system to explore how parasitism may change the regulation of amino acids in A. gossypii with UHPLC-MS/MS and RT-qPCR techniques. Here, for the first 8 h of parasitism the abundance of almost all amino acids in cotton aphids increased, and after 16 h most of the amino acids decreased. An amino acid of parasitic syndrome, the content of Tyr increased gradually after being parasitized. The expression of genes related to amino acid metabolism increased significantly in early stages of parasitism and then significantly decreased gradually. At the same time, the abundance of Buchnera, a cotton aphid specific symbiont increased significantly. Our comprehensive analyses reveal impacts of B. communis on the amino acid regulatory network in cotton aphid from three aspects: amino acid metabolism, gene expression, and bacterial symbionts. Therefore, this research provides an important theoretical basis for parasitoid nutritional regulation in host, which is highly significant as it may inform the artificial reproduction of parasitoids and the biological control of insect pests.